2014
DOI: 10.1002/rcm.6870
|View full text |Cite
|
Sign up to set email alerts
|

Predicting collision-induced dissociation spectra: Semi-empirical calculations as a rapid and effective tool in software-aided mass spectral interpretation

Abstract: Cleavage of the polarised bonds appears to result from protonation on the more electronegative atom of the bond, inducing conformational changes leading to bond weakening. AM1-calculated bond length changes act as a descriptor for predicting bond cleavage. However, the impetus for cleavage of the unpolarised bonds may be product ion stability rather than bond weakening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
0
22
0
1
Order By: Relevance
“…Under these circumstances, further analysis was needed to match a specific [M + H] + ion of 1a with the initial fragmentation process in each of the four distinct pathways. Recently, bond elongation upon protonation has been proposed as a predictor of polarized bond cleavage during CID . Changes in bond lengths resulting from protonation of a nitrogen atom in 1 (ol) or 1 (one) were determined from the DFT optimized structures of 1a (ol) and 1a (one) with respect to the neutral tautomer in a similar conformation (Table S6, supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Under these circumstances, further analysis was needed to match a specific [M + H] + ion of 1a with the initial fragmentation process in each of the four distinct pathways. Recently, bond elongation upon protonation has been proposed as a predictor of polarized bond cleavage during CID . Changes in bond lengths resulting from protonation of a nitrogen atom in 1 (ol) or 1 (one) were determined from the DFT optimized structures of 1a (ol) and 1a (one) with respect to the neutral tautomer in a similar conformation (Table S6, supporting information).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it may be concluded that the collision energy is not required to move the proton to the dissociative site to initiate cleavage via bond elongation. Therefore, protonation‐induced bond elongation required for fragmentation during CID on its own is not sufficient to trigger bond cleavage. Fragmentation is collision energy dependent but proton migration does not depend on collision energy.…”
Section: Discussionmentioning
confidence: 99%
“…This can be used predictively as the computational analysis of the structure only is required to find the bonds with the potential to cleave. In one study, [ 33 ] 15 compounds (98 observed bond cleavages and over 8000 bond length calculations) were used to confirm that significant bond elongation (>0.039 Å for these compounds) may be used as a descriptor for cleavage of polarised bonds during CID. In this study a 100% success rate was achieved in the prediction of polarised bond cleavage.…”
mentioning
confidence: 99%
“…For example, the number of predicted compounds from a database search can be reduced by excluding compounds with predicted MS/MS spectra that do not match the observed [94]. Advancements in predictive fragmentation are being developed [95][96][97][98][99][100][101] and have been reviewed previously [76]. Examples of MS/MS fragmentation prediction tools include, but are not limited to, ACD/MS Fragmenter [102], MolFind [94], MetFrag [101], MIDAS (Metabolite Identification via Database Searching) [103] and SmartMass [91].…”
Section: Tandem Mass Spectrometrymentioning
confidence: 97%